Characteristics and prognosis of isolated aortic valve infective endocarditis in patients with bicuspid aortic valves: a propensity matched study - Bohbot, Yohann; Denev, Seyhan; Benvenga, Rossella M.; Philip, Mary; Michelena, Hector I.; Citro, Rodolfo; Habib, Gilbert; Tribouilloy, Christophe (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Bicuspid aortic valve (BAV) is the most common congenital heart disease with an increased risk of infective endocarditis (IE). Few data are available on isolated native BAV-IE. The aim of this study was to compare patients with tricuspid aortic valve (TAV) IE and BAV-IE in terms of characteristics, management and prognosis.We included 728 consecutive patients with IE on isolated native aortic valve in 3 centres: Amiens and Marseille Hospitals in France and Salerno Hospital in Italy. We studied in hospital and long-term mortality before and after matching for age, sex and comorbidity index. Median follow-up was 67.2 [IQR: 19-120] months.Results: Of the 728 patients, 123 (16.9%) had BAV. Compared with patients with TAV-IE, patients with BAV-IE were younger, had fewer co-morbidities and were more likely to be male.They presented more major neurological events and perivalvular complications (both p<0.05).Early surgery (<30 days) was performed in 52% of BAV-IE cases vs. 42.8% for TAV-IE (p=0.061). The 10-year survival rate was 74±5% in BAV-IE patients compared with 66±2% in TAV-IE patients (p=0.047). After propensity score matching (for age, gender and comorbidities), there was no difference in mortality between the two groups, with an estimated 10-year survival of 73±5% versus 76±4% respectively (p=0.91).BAV is a frequent finding in patients with isolated aortic valve IE and is associated with more perivalvular complications and neurological events. The differences in survival with TAV-IE are probably related to the age and comorbidity differences between these two populations.